Selective Labeling of Individual Neurons in Dense Cultured Networks With Nanoparticle-Enhanced Photoporation - Xiong, Ranhua; Verstraelen, Peter; Demeester, Jo; Skirtach, Andre G.; Timmermans, Jean-Pierre; De Smedt, Stefaan C.; De Vos, Winnok H.; Braeckmans, Kevin (Frontiers in Cellular Neuroscience, 2018)
Neurodevelopmental and neurodegenerative disorders are characterized by subtle alterations in synaptic connections and perturbed neuronal network functionality. A hallmark of neuronal connectivity is the presence of dendritic spines, micron-sized protrusions of the dendritic shaft that compartmentalize single synapses to fine-tune synaptic strength. However, accurate quantification of spine density and morphology in mature neuronal networks is hampered by the lack of targeted labeling strategies. To resolve this, we have optimized a method to deliver cell-impermeable compounds into selected cells based on Spatially resolved NAnoparticle-enhanced Photoporation (SNAP). We show that SNAP enables efficient labeling of selected individual neurons and their spines in dense cultured networks without causing cytotoxicity. We compare SNAP with widely used spine labeling techniques such as the application of lipophilic dyes and genetically encoded fluorescent markers. Using SNAP, we demonstrate a time-dependent increase in spine density in healthy cultures as well as a reduction in spine density after chemical mimicry of hypoxia. Since, the sparse labeling procedure can be automated using an intelligent acquisition scheme, SNAP holds promise for high-content screening campaigns of neuronal connectivity in the context of neurodevelopmental and neurodegenerative disorders.